2014
DOI: 10.1038/bmt.2014.176
|View full text |Cite
|
Sign up to set email alerts
|

An update on allogeneic hematopoietic progenitor cell transplantation for myeloproliferative neoplasms in the era of tyrosine kinase inhibitors

Abstract: Myeloproliferative neoplasms are a category of diseases that have been traditionally amenable to allogeneic hematopoietic progenitor cell transplantation. Current developments in drug therapy have delayed transplantation for more advanced phases of the disease, especially for patients with CML, whereas transplantation remains a mainstream treatment modality for patients with advanced myelofibrosis and chronic myelomonocytic leukemia. Reduced-intensity conditioning has decreased the treatmentrelated mortality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have suggested that AMPK is a potential target that regulates various signaling pathways [ 32 ]. In addition, AMPK activators can suppress several types of tumors [ 33 ]. mTOR is known to play a central role in antitumor activity among the signaling pathways regulated by AMPK [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that AMPK is a potential target that regulates various signaling pathways [ 32 ]. In addition, AMPK activators can suppress several types of tumors [ 33 ]. mTOR is known to play a central role in antitumor activity among the signaling pathways regulated by AMPK [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, tyrosine kinase inhibitors targeting the BCR-ABL fusion protein, including imatinib, dasatinib and nilotinib, are used for CML treatment, and have demonstrated improved outcomes in patients with CML (20). However, high relapse rates, drug resistance and high mortality rates associated with transplantation remain challenges for CML treatment (21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that AMPK activators can suppress several types of tumors, including pancreatic, bladder and prostate cancer, through AMPK-dependent apoptosis (19)(20)(21). In addition, AMPK has been reported as a potential target that regulates various signaling pathways, subsequently exhibiting antileukemia activity (22).…”
Section: Discussionmentioning
confidence: 99%
“…(29) However, allo-SCT for this disease has been associated with higher treatment-related mortality (TRM) and relapse rates, and, in general, worse outcomes than for other myeloproliferative neoplasms. (10) Data regarding allo-SCT outcomes in patients with CMML are currently limited to small retrospective series, and no prospective studies have been performed for CMML patients because of the relatively low number of patients with CMML treated with allogeneic transplantation. Moreover, timing of allo-SCT and benefit of induction therapy, in particular treatment with a hypomethylating agent before transplant, has not been studied.…”
Section: Introductionmentioning
confidence: 99%